A Pt@PtNi@Pt core-shell structure nanowire, preparation method and application thereof
By using Pt@PtNi@Pt core-shell structure nanowires in the electrocatalyst and using H2 to induce Pt segregation to form Pt shell, the problem of insufficient efficiency and durability of electrocatalysts for hydrogen production in water is solved, and more efficient and stable Hydrogen production.
Patent Information
- Application Number
- CN202411232187.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-04
AI Technical Summary
In the prior art, the electrocatalyst efficiency and durability of hydrogen produced by electrolyzing water are insufficient, which limits the wide application of hydrogen energy in the energy field.
Pt@PtNi@Pt core-shell structure nanowires are used as electrocatalysts, and Pt segregation is induced by small gas molecule H2 as structural guides to form Pt shells, increasing the Pt site on the surface of the nanowires and preventing the dissolution of Ni elements, thereby enhancing the activity of the catalyst. and stability.
The intrinsic activity and structural stability of the catalyst are improved, and the efficiency and durability of hydrogen production by electrolyzing water are improved.
Smart Images

Figure CN118720160B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalyst preparation, and in particular to a Pt@PtNi@Pt core-shell structure nanowire, a preparation method and application thereof. Background Art
[0002] Hydrogen is a high energy density, environmentally friendly, renewable clean energy, and is considered one of the potential options for future fuels. However, industrial hydrogen production mainly relies on fossil fuels, which will cause environmental pollution. Therefore, finding a fossil fuel-free H2 production method has become an important research direction.
[0003] At present, a variety of methods for preparing H2 have been developed, including petroleum / naphtha reforming, methane steam reforming, coal gasification and water electrolysis. Among them, water electrolysis is considered to be the cleanest method of hydrogen production. The large-scale and sustainable production of H2 requires the development of efficient and low-cost hydrogen evolution reaction (HER) electrocatalysts to promote the widespread application of hydrogen in the energy field. Therefore, the development of low-cost and high-efficiency electrocatalysts is crucial to promote the development of water electrolysis hydrogen production technology, which is of great significance for the realization of large-scale water electrolysis hydrogen production technology. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a Pt@PtNi@Pt core-shell structure nanowire, a preparation method and an application thereof, so as to improve the activity and durability of the Pt@PtNi@Pt core-shell structure nanowire, thereby improving the efficiency of hydrogen production by electrolysis of water.
[0005] The present invention provides a method for preparing Pt@PtNi@Pt core-shell structure nanowires, comprising the following steps:
[0006] S100, mixing oleylamine and octadecene to obtain a first mixed solution; adding Pt(acac)2, Ni(acac)2, hexadecyltrimethylammonium bromide and glucose to the first mixed solution, and subjecting the mixture to ultrasonic treatment for 0.5 hour to 3 hours to obtain a second mixed solution;
[0007] S200, adding the second mixed solution into a high-pressure reactor, wherein the high-pressure reactor is in a mixed gas environment consisting of hydrogen and argon, and the content of hydrogen in the mixed gas is 10% to 40%;
[0008] S300, heating the second mixed solution to 180° C. to 220° C. by a high-pressure reactor and keeping the temperature for 20 to 30 hours, cooling to room temperature, and washing with a mixed solution of n-hexane and ethanol to obtain Pt@PtNi@Pt;
[0009] S400, dispersing superconducting carbon black in ethanol by ultrasonic treatment to obtain a first dispersion; dispersing Pt@PtNi@Pt in n-hexane by ultrasonic treatment to obtain a second dispersion; and dropping the second dispersion into the first dispersion to obtain a third mixed solution;
[0010] S500, centrifuging the third mixed solution to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst under normal temperature and vacuum conditions to obtain Pt@PtNi@Pt core-shell structured nanowires.
[0011] According to a method for preparing Pt@PtNi@Pt core-shell structure nanowires provided by the present invention, in the step S100, the volume of the oleylamine is 4 mL~8 mL; the volume of the octadecene is 4 mL~8 mL.
[0012] According to a method for preparing Pt@PtNi@Pt core-shell structure nanowires provided by the present invention, in the step S100, the mass of the Pt(acac)2 is 8mg~12mg, the mass of the Ni(acac)2 is 5mg~10mg, the mass of the hexadecyltrimethylammonium bromide is 35mg~45mg, and the mass of the glucose is 50mg~70mg.
[0013] According to a method for preparing Pt@PtNi@Pt core-shell structured nanowires provided by the present invention, in the step S200, the pressure in the high-pressure reactor is 0.1MPa~0.4MPa; and the volume of the high-pressure reactor is 20mL~30mL.
[0014] According to a method for preparing a Pt@PtNi@Pt core-shell structure nanowire provided by the present invention, in the step S200, before adding the second mixed solution into the autoclave, the method further comprises:
[0015] For the pretreatment of the autoclave, the mixed gas is introduced into the autoclave for 20 to 40 minutes to remove the air in the autoclave.
[0016] According to a method for preparing Pt@PtNi@Pt core-shell structure nanowires provided by the present invention, in the step S300, the volume ratio of the n-hexane to the ethanol is 1:1-1:5.
[0017] According to a method for preparing a Pt@PtNi@Pt core-shell structure nanowire provided by the present invention, in the step S400, the mass of the superconducting carbon black is 5 mg to 10 mg, and the volume of the ethanol is 15 mL to 20 mL;
[0018] The volume of the n-hexane is 5 mL to 20 mL.
[0019] According to a method for preparing a Pt@PtNi@Pt core-shell structure nanowire provided by the present invention, in the step S500, the rotation speed of the centrifugal treatment is 6000r / min~100000r / min; the time of the centrifugal treatment is 4 minutes~10 minutes;
[0020] The drying time is 8 to 12 hours.
[0021] The present invention also provides a Pt@PtNi@Pt core-shell structure nanowire, which is prepared based on the above-mentioned method for preparing the Pt@PtNi@Pt core-shell structure nanowire.
[0022] The present invention also provides an application of a Pt@PtNi@Pt core-shell structure nanowire, wherein the Pt@PtNi@Pt core-shell structure nanowire is used as an electrocatalyst in the electrolysis of water to produce hydrogen.
[0023] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:
[0024] The Pt@PtNi@Pt core-shell structure nanowires, preparation methods and applications provided by the present invention use small gas molecules H2 as a structure-directing agent to induce Pt segregation, thereby changing the metal surface free energy to adjust the surface composition of the catalyst, causing Pt to segregate to the surface to form a Pt shell, which not only increases the Pt sites on the surface of the nanowires, but also prevents the Ni element inside the nanowires from being dissolved during the catalytic process, thereby improving the intrinsic activity of the catalyst and the stability of the structure.
[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram comparing the XRD patterns of Example 1, Comparative Example 2 and Comparative Example 4 provided by the present invention.
[0028] Figure 2 This is a HAADF-STEM image of the Pt@PtNi@Pt core-shell structure nanowire provided by the present invention.
[0029] Figure 3It is the LSV curve corresponding to the HER test results of Example 1 and Comparative Examples 1, 2, 3 and 4 provided by the present invention in a potassium hydroxide solution with a concentration of 1 M.
[0030] Figure 4 These are the chronopotentiometric curves of Example 1, Comparative Examples 2 and 4 provided by the present invention.
[0031] Figure 5 It is a comparative schematic diagram of TEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 provided by the present invention.
[0032] Figure 6 It is a comparative schematic diagram of TEM images of Pt@PtNi@Pt core-shell structure nanowires prepared by the high-pressure reactor provided by the present invention at different pressures.
[0033] Reference numerals:
[0034] 1. Pt shell; 2. Pt nanowire; 3. PtNi intermediate layer. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.
[0036] In the description of the embodiments of the present invention, it should be noted that the terms “first”, “second” and “third” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0037] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0038] The present invention provides a Pt@PtNi@Pt core-shell structure nanowire, a preparation method and application thereof.
[0039] The present invention provides a method for preparing a Pt@PtNi@Pt core-shell structure nanowire, comprising the following steps:
[0040] S100. Evenly mix 4 mL to 8 mL of oleylamine and 4 mL to 8 mL of octadecene to obtain a first mixed solution; add 8 mg to 12 mg of Pt(acac)2, 5 mg to 10 mg of Ni(acac)2, 35 mg to 45 mg of hexadecyltrimethylammonium bromide and 50 mg to 70 mg of glucose to the first mixed solution, and ultrasonically treat the solution for 0.5 hour to 3 hours to obtain a second mixed solution; it should be noted that ultrasonic treatment refers to mixing the solution under the vibration of an ultrasonic cleaning machine to improve the uniformity of mixing.
[0041] S200, pre-treat the autoclave by passing the mixed gas into the autoclave for 20 minutes to 40 minutes, completely excluding the air in the autoclave to prevent the oxygen in the air from affecting the reaction in the autoclave. The volume of the autoclave is 20mL to 30mL.
[0042] The second mixed solution is added to the pretreated autoclave, and the autoclave is a mixed gas environment composed of hydrogen and argon, and the content of hydrogen in the mixed gas is 10%~40%. That is to say, after the second mixed solution is added to the pretreated autoclave, a mixed gas is introduced into the autoclave, wherein hydrogen is used as a reaction gas and argon is used as an inert protective gas. Hydrogen is used as a structure-directing agent to induce Pt segregation, and the reaction is more likely to form Pt@PtNi@Pt three-layer core-shell structure nanowires. Thermodynamically, H2 can adjust the surface composition of the catalyst by changing the surface free energy of the metal, prompting Pt to segregate to the surface to form a Pt shell. The formation of the Pt shell not only increases the Pt sites on the surface of the nanowire, but also prevents the Ni element inside the nanowire from being dissolved during the catalytic process, thereby improving the intrinsic activity and structural stability of the catalyst. The introduction of Ni causes compressive strain and electron transfer in the surface Pt, solving the problem of excessive adsorption of H* by pure Pt catalyst.
[0043] The pressure in the high-pressure reactor is 0.1 MPa to 0.4 MPa, preferably 0.1 MPa.
[0044] Furthermore, the use of argon as the protective gas is more conducive to forming a double-layer core-shell structure with Pt as the core and PtNi alloy as the shell.
[0045] S300, heating the second mixed solution to 180°C~220°C by a high-pressure reactor and keeping it warm for 20 hours~30 hours, cooling it to room temperature, and washing it with a mixed solution of n-hexane and ethanol in a volume ratio of 1:1~1:5 to obtain Pt@PtNi@Pt.
[0046] S400. Disperse 5 mg to 10 mg of superconducting carbon black in 15 mL to 20 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt@PtNi@Pt in 5 mL to 20 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 0.5 hour to 3 hours for standby use.
[0047] S500, centrifuging the third mixed solution at a speed of 6000 r / min to 10000 r / min for 4 to 10 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum for 8 to 12 hours to obtain Pt@PtNi@Pt core-shell structured nanowires.
[0048] Example 1
[0049] S100, 6 mL of oleylamine and 6 mL of octadecene were mixed evenly to obtain a first mixed solution; 10 mg of Pt(acac)2, 10 mg of Ni(acac)2, 40 mg of hexadecyltrimethylammonium bromide and 60 mg of glucose were added to the first mixed solution, and ultrasonically treated for 1 hour to obtain a second mixed solution;
[0050] S200, pre-treating the autoclave by passing the mixed gas into the autoclave for 30 minutes to completely remove the air in the autoclave to prevent the oxygen in the air from affecting the reaction in the autoclave.
[0051] The second mixed solution is added into the pretreated autoclave, the autoclave is in a mixed gas environment consisting of hydrogen and argon, the content of hydrogen in the mixed gas is 20%, and the pressure in the autoclave is 0.1 MPa.
[0052] S300, heating the second mixed solution to 190° C. in a high-pressure reactor and keeping the temperature for 24 hours, cooling to room temperature, and washing with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3 to obtain Pt@PtNi@Pt.
[0053] S400. Disperse 8 mg of superconducting carbon black in 18 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt@PtNi@Pt in 10 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 1 hour for later use.
[0054] S500, centrifuging the third mixed solution at a speed of 8000 r / min for 6 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum environment for 10 hours to obtain Pt@PtNi@Pt core-shell structured nanowires.
[0055] Comparative Example 1
[0056] S100, 6 mL of oleylamine and 6 mL of octadecene were mixed evenly to obtain a first mixed solution; 10 mg of Pt(acac)2, 4 mg of Ni(acac)2, 40 mg of hexadecyltrimethylammonium bromide and 60 mg of glucose were added to the first mixed solution, and ultrasonically treated for 1 hour to obtain a second mixed solution;
[0057] S200, adding the second mixed solution into an oil bath, and maintaining the reaction process in an argon environment.
[0058] S300, heating the second mixed solution to 190°C in an oil bath and keeping it warm for 24 hours, cooling it to room temperature, and washing it with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3 to obtain Pt@Pt5Ni2.
[0059] S400. Disperse 8 mg of superconducting carbon black in 18 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt@Pt5Ni2 in 10 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 1 hour for later use.
[0060] S500, centrifuging the third mixed solution at a speed of 8000 r / min for 6 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum environment for 10 hours to obtain Pt@Pt5Ni2 nanowires.
[0061] Comparative Example 2
[0062] S100, 6 mL of oleylamine and 6 mL of octadecene were mixed evenly to obtain a first mixed solution; 10 mg of Pt(acac)2, 8 mg of Ni(acac)2, 40 mg of hexadecyltrimethylammonium bromide and 60 mg of glucose were added to the first mixed solution, and ultrasonically treated for 1 hour to obtain a second mixed solution;
[0063] S200, adding the second mixed solution into an oil bath, and maintaining the reaction process in an argon environment.
[0064] S300, heating the second mixed solution to 190°C in an oil bath and keeping it warm for 24 hours, cooling it to room temperature, and washing it with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3 to obtain Pt@Pt5Ni4.
[0065] S400. Disperse 8 mg of superconducting carbon black in 18 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt@Pt5Ni4 in 10 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 1 hour for later use.
[0066] S500, centrifuging the third mixed solution at a speed of 8000 r / min for 6 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum environment for 10 hours to obtain Pt@Pt5Ni4 nanowires.
[0067] Comparative Example 3
[0068] S100, 6 mL of oleylamine and 6 mL of octadecene were mixed evenly to obtain a first mixed solution; 10 mg of Pt(acac)2, 12 mg of Ni(acac)2, 40 mg of hexadecyltrimethylammonium bromide and 60 mg of glucose were added to the first mixed solution, and ultrasonically treated for 1 hour to obtain a second mixed solution;
[0069] S200, adding the second mixed solution into an oil bath, and maintaining the reaction process in an argon environment.
[0070] S300, heating the second mixed solution to 190°C in an oil bath and keeping it warm for 24 hours, cooling it to room temperature, and washing it with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3 to obtain Pt@Pt5Ni6.
[0071] S400. Disperse 8 mg of superconducting carbon black in 18 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt@Pt5Ni6 in 10 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 1 hour for later use.
[0072] S500, centrifuging the third mixed solution at a speed of 8000 r / min for 6 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum environment for 10 hours to obtain Pt@Pt5Ni6 nanowires.
[0073] Comparative Example 4
[0074] S100, 6 mL of oleylamine and 6 mL of octadecene were mixed evenly to obtain a first mixed solution; 10 mg of Pt(acac)2, 40 mg of hexadecyltrimethylammonium bromide and 60 mg of glucose were added to the first mixed solution, and ultrasonically treated for 1 hour to obtain a second mixed solution;
[0075] S200, adding the second mixed solution into an oil bath, and maintaining the reaction process in an argon environment.
[0076] S300, heating the second mixed solution to 190° C. in an oil bath and keeping the temperature for 24 hours, cooling to room temperature, and washing with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3 to obtain Pt.
[0077] S400. Disperse 8 mg of superconducting carbon black in 18 mL of ethanol by ultrasonic treatment to obtain a first dispersion; disperse Pt in 10 mL of n-hexane by ultrasonic treatment to obtain a second dispersion; add the second dispersion dropwise into the first dispersion to obtain a third mixed solution; and perform ultrasonic treatment on the third mixed solution for 1 hour for later use.
[0078] S500, centrifuging the third mixed solution at a speed of 8000 r / min for 6 minutes to obtain a carbon-loaded catalyst; drying the carbon-loaded catalyst at room temperature and in a vacuum environment for 10 hours to obtain Pt nanowires.
[0079] like Figure 1As shown, the XRD spectrum comparison schematic diagram of Example 1 of the present invention and Comparative Examples 2 and 4. It can be seen that the peak position of the Pt nanowire is very consistent with the peak position of the standard card Pt, while the (111) peak position of the Pt@Pt5Ni4 nanowire has shifted to the right, which indicates that the Ni element is successfully inserted into the Pt element, resulting in a decrease in the (111) crystal plane spacing, causing compressive strain in the Pt phase.
[0080] After H2 induction, Pt segregation occurred, and the (111) peak shift of Pt@PtNi@Pt nanowires was smaller than that of Pt@Pt5Ni4 nanowires. This Pt segregation led to the appearance of more pure Pt phase.
[0081] like Figure 2 As shown in the figure, the HAADF-STEM image of the Pt@PtNi@Pt core-shell structure nanowire provided by the present invention. It can be seen that the innermost layer of the Pt@PtNi@Pt core-shell structure nanowire has an extremely thin Pt nanowire 2, followed by a transition layer with a lighter color, which is composed of PtNi alloy, that is, PtNi intermediate layer 3. The color of the outermost layer is brighter than that of the inner layer. Through analysis, it can be found that the Pt element content in the shell layer is higher, that is, Pt shell 1.
[0082] like Figure 3 As shown, the LSV curves corresponding to the HER test results of Example 1 and Comparative Examples 1, 2, 3 and 4 in a potassium hydroxide solution with a concentration of 1 M are shown. It can be seen that the Pt@PtNi@Pt core-shell structure nanowire first appears current, and as the overpotential continues to increase, the current density of the Pt@PtNi@Pt core-shell structure nanowire is still higher than that of Comparative Examples 1, 2, 3 and 4. By observing the current density of the LSV curve, it can also be seen that the Pt@PtNi@Pt core-shell structure nanowire has the best HER activity.
[0083] like Figure 4 As shown, Example 1 of the present invention and Comparative Example 2 and Comparative Example 4 have a 2 Chronopotentiometry curves under current density. It can be seen that the overpotential of Pt nanowires, Pt@Pt5Ni4 nanowires and Pt@PtNi@Pt core-shell nanowires increased by 226.3 mV, 66.6 mV and 38.7 mV respectively after 12 hours of constant current test. Pt@PtNi@Pt core-shell nanowires have the best stability.
[0084] like Figure 5 As shown, TEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. Among them, Figure 5a is the TEM image of Comparative Example 4, b is the TEM image of Comparative Example 1, c is the TEM image of Comparative Example 2, and d is the TEM image of Comparative Example 3. It can be seen that Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 all present obvious nanowire morphology, but the linear shapes of the nanowires are different. Among them, the shape of Comparative Example 4 (Pt nanowire) is a relatively uniform linear shape with a diameter (6 nm~7 nm), and a small amount of nanoparticles exist at both ends of the Pt nanowire.
[0085] Comparative Examples 1, 2, and 3 are nanowires containing Ni. Unlike Comparative Example 4, after adding Ni, the nanowires are chain-shaped, connected by a nanowire in the center, connecting the nanospheres together to form a nanowire. It can be observed that as the Ni content increases, the nanowires gradually agglomerate.
[0086] like Figure 6 As shown, a schematic diagram of the comparison of TEM images of Pt@PtNi@Pt core-shell structure nanowires prepared in a high-pressure reactor at different pressures. Figure 6 Figure a is a TEM image of Pt@PtNi@Pt core-shell structure nanowires prepared at a pressure of 0.1MPa in the autoclave, b is a TEM image of Pt@PtNi@Pt core-shell structure nanowires prepared at a pressure of 0.2MPa in the autoclave, c is a TEM image of Pt@PtNi@Pt core-shell structure nanowires prepared at a pressure of 0.3MPa in the autoclave, and d is a TEM image of Pt@PtNi@Pt core-shell structure nanowires prepared at a pressure of 0.4MPa in the autoclave. It can be seen that with the increase of the pressure in the autoclave, the shape of the Pt@PtNi@Pt core-shell structure nanowires gradually disappears until the pressure in the autoclave is 0.4MPa to form nanoparticles. It can be seen that when the pressure in the autoclave is 0.1MPa and the hydrogen content in the mixed gas is 20%, the shape of the nanowires formed is the best. However, compared with the Pt@Pt5Ni4 nanowires (see Figure 5 (c) The diameter of the synthesized Pt@PtNi@Pt core-shell structured nanowires increased significantly after pressurization.
[0087] The present invention also provides a Pt@PtNi@Pt core-shell structure nanowire, which is prepared based on the above-mentioned method for preparing a Pt@PtNi@Pt core-shell structure nanowire. The overpotential of the Pt@PtNi@Pt core-shell structure nanowire in a 1M potassium hydroxide solution is 15.6mV, which is 3.2mV lower than that of the Pt@Pt5Ni4 core-shell structure nanowire with a PtNi alloy as the shell layer. Moreover, the overpotential of the Pt@PtNi@Pt core-shell structure nanowire only increased by 2.8mV after 5000 cycles.
[0088] The present invention also provides an application of a Pt@PtNi@Pt core-shell structure nanowire, wherein the Pt@PtNi@Pt core-shell structure nanowire is used as an electrocatalyst in the electrolysis of water to produce hydrogen.
[0089] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:
[0090] The Pt@PtNi@Pt core-shell structure nanowires, preparation methods and applications provided by the present invention use small gas molecules H2 as a structure-directing agent to induce Pt segregation, thereby changing the metal surface free energy to adjust the surface composition of the catalyst, causing Pt to segregate to the surface to form a Pt shell, which not only increases the Pt sites on the surface of the nanowires, but also prevents the Ni element inside the nanowires from being dissolved during the catalytic process, thereby improving the intrinsic activity of the catalyst and the stability of the structure.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing Pt@PtNi@Pt core-shell structure nanowires, characterized in that: The steps include: S100, mixing oleylamine and octadecene to obtain a first mixed solution; adding Pt(acac)2, Ni(acac)2, hexadecyltrimethylammonium bromide and glucose to the first mixed solution, and subjecting the mixture to ultrasonic treatment for 0.5 hour to 3 hours to obtain a second mixed solution; S200, adding the second mixed solution into a high-pressure reactor, wherein the high-pressure reactor is in a mixed gas environment consisting of hydrogen and argon, and the content of hydrogen in the mixed gas is 10% to 40%; S300, heating the second mixed solution to 180° C. to 220° C. by a high-pressure reactor and keeping the temperature for 20 to 30 hours, cooling to room temperature, and washing with a mixed solution of n-hexane and ethanol to obtain Pt@PtNi@Pt; S400, dispersing superconducting carbon black in ethanol by ultrasonic treatment to obtain a first dispersion; dispersing Pt@PtNi@Pt in n-hexane by ultrasonic treatment to obtain a second dispersion; and dropping the second dispersion into the first dispersion to obtain a third mixed solution; S500, centrifuging the third mixed solution to obtain a carbon-supported catalyst; The carbon-supported catalyst is dried under normal temperature and vacuum conditions to obtain Pt@PtNi@Pt core-shell structured nanowires.
2. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S100, the volume of the oleylamine is 4 mL to 8 mL; the volume of the octadecene is 4 mL to 8 mL.
3. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S100, the mass of the Pt(acac)2 is 8mg~12mg, the mass of the Ni(acac)2 is 5mg~10mg, the mass of the hexadecyltrimethylammonium bromide is 35mg~45mg, and the mass of the glucose is 50mg~70mg.
4. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S200, the pressure in the high-pressure reactor is 0.1 MPa to 0.4 MPa; and the volume of the high-pressure reactor is 20 mL to 30 mL.
5. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S200, before adding the second mixed solution into the autoclave, the process further includes: For the pretreatment of the autoclave, the mixed gas is introduced into the autoclave for 20 to 40 minutes to remove the air in the autoclave.
6. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S300, the volume ratio of the n-hexane to the ethanol is 1:1 to 1:
5.
7. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S400, the mass of the superconducting carbon black is 5 mg to 10 mg, and the volume of the ethanol is 15 mL to 20 mL; The volume of the n-hexane is 5 mL to 20 mL.
8. The method for preparing Pt@PtNi@Pt core-shell structure nanowires according to claim 1, characterized in that: In the step S500, the rotation speed of the centrifugal treatment is 6000 r / min to 100000 r / min; the time of the centrifugal treatment is 4 minutes to 10 minutes; The drying time is 8 to 12 hours.
9. A Pt@PtNi@Pt core-shell structure nanowire, characterized in that: It is prepared based on the preparation method of Pt@PtNi@Pt core-shell structure nanowires as described in any one of claims 1 to 8.
10. An application of Pt@PtNi@Pt core-shell structure nanowires, characterized in that: The Pt@PtNi@Pt core-shell structure nanowires as claimed in claim 9 are used as electrocatalysts in the electrolysis of water to produce hydrogen.
Citation Information
Patent Citations
Pt-based nanowire cathode catalyst for in-vehicle fuel cell and preparation method thereof
CN106972181A
Mesoporous platinum-platinum-nickel core-shell framework nanowire and preparation method thereof
CN116154189A